1986
DOI: 10.1182/blood.v68.6.1207.bloodjournal6861207
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity of type IIA von Willebrand's disease: studies with protease inhibitors

Abstract: The absence of large von Willebrand factor (vWF) multimers from plasma is a characteristic of Type IIA von Willebrand's disease (vWD) and is thought to contribute to the clinical expression of this disorder. Recently, three IIA patients have been reported in whom intermediate and large multimers could be restored if blood were collected in 5 mm EDTA, 6 mmol/L N-ethylmaleimide, and 1 mmol/L leupeptin. This suggested that absence of large multimers resulted from in vitro proteolysis. We have now collected blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A poor and short-lasting response is seen in patients with type 1 vWD with low platelet vWF. In type 2A vWD, FVIII:C levels are usually increased by DDAVP, but the BT is shortened in only a few patients [7]. A poor response would be predicted in type 2M because vWF is dysfunctional in this subtype.…”
Section: Indications For Use Of Ddavpmentioning
confidence: 99%
“…A poor and short-lasting response is seen in patients with type 1 vWD with low platelet vWF. In type 2A vWD, FVIII:C levels are usually increased by DDAVP, but the BT is shortened in only a few patients [7]. A poor response would be predicted in type 2M because vWF is dysfunctional in this subtype.…”
Section: Indications For Use Of Ddavpmentioning
confidence: 99%
“…These mutations cause the absence of large vWF multimers either by impairing multimer assembly within the cell or by promoting the clearance of large multimers from the circulation. possibly by proteolysis [23]. A distinct set of mutations within the vWF propeptide causes a recessive form of vWD Type 2A by impairing multimer assembly [23.24].…”
Section: Vwdnjpe2amentioning
confidence: 99%
“…In patients with type 1 vWd with normal platelet vWf, the prolonged bleeding time is usually corrected [1-6]. Some studies have described hemostatic improvement after DDAVP in type 2A vWd, while others studies have shown a lack of benefit in type 2A vWd [7,81. DDAVP therapy is not considered a useful and/or safe form of therapy in type 2B vWd since its administration has been associated with thrombocytopenia and circulating platelet aggregates [9-131. To determine the effect(s) of DDAVP on platelet counts in type 2B vWd, we have administered DDAVP to three type 2B vWd patients with different missense mutations and examined their hemostatic response(s).…”
Section: -Desamino-8-d-arginine-vasopressin (Ddavp) Infusion Increasmentioning
confidence: 99%